2015
DOI: 10.31887/dcns.2015.17.2/cagudelo
|View full text |Cite
|
Sign up to set email alerts
|

Applications of magnetic resonance imaging for treatment-resistant late-life depression

Abstract: Late-life depression (LLD) is a growing public and global health concern with diverse clinical manifestations and etiology. This literature review summarizes neuroimaging findings associated with depression in older adults and treatment-response variability. LLD has been associated with cerebral atrophy, diminished myelin integrity, and cerebral lesions in frontostriatal-limbic regions. These associations help explain the depression-executive dysfunction syndrome observed in LLD, and support cerebrovascular bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 154 publications
(182 reference statements)
0
2
0
Order By: Relevance
“…Moreover, such a vascular etiology may explain the high recurrence and persistence rate of LLD, in addition to high treatment resistance to antidepressant and/or behavioral therapy [ 34 , 35 , 36 ]. Later, the term “MRI-defined VaD” was introduced [ 37 ], with a focus on the presence and severity of either white matter changes or subcortical gray matter lesions (lacunes, microbleeds), supporting the hypothesis that loss of brain volume, diminished white matter integrity, and lesions in the fronto–striatal–limbic regions are associated with depressive symptoms in the elderly [ 38 , 39 , 40 , 41 ], although this was not confirmed by others [ 42 , 43 , 44 , 45 , 46 ].…”
Section: The “Vascular Depression Hypothesis”mentioning
confidence: 99%
“…Moreover, such a vascular etiology may explain the high recurrence and persistence rate of LLD, in addition to high treatment resistance to antidepressant and/or behavioral therapy [ 34 , 35 , 36 ]. Later, the term “MRI-defined VaD” was introduced [ 37 ], with a focus on the presence and severity of either white matter changes or subcortical gray matter lesions (lacunes, microbleeds), supporting the hypothesis that loss of brain volume, diminished white matter integrity, and lesions in the fronto–striatal–limbic regions are associated with depressive symptoms in the elderly [ 38 , 39 , 40 , 41 ], although this was not confirmed by others [ 42 , 43 , 44 , 45 , 46 ].…”
Section: The “Vascular Depression Hypothesis”mentioning
confidence: 99%
“…Selective serotonin reuptake inhibitor(SSRIS) are the first-line treatment for LLD, but approximately one-third of the LLD patients experience treatment resistance (Agudelo, Aizenstein, Karp, & Reynolds, 2015). Evidence has shown that the pharmacologic treatment response of LOD is worse than that of EOD (Naismith, Norrie, Mowszowski, & Hickie, 2012).…”
Section: Introductionmentioning
confidence: 99%